Design and simulation of novel laparoscopic renal denervation system: a feasibility study. (31st December 2018) - Ye, Eunbi; Baik, Jinhwan; Lee, Seunghyun; Ryu, Seon Young; Yang, Sunchoel; Choi, Eue-Keun; Song, Won Hoon; Yuk, Hyeong Dong; Jeong, Chang Wook; Park, Sung-Min
Abstract: Purpose: In this study, we propose a novel laparoscopy-based renal denervation (RDN) system for treating patients with resistant hypertension. In this feasibility study, we investigated whether our proposed surgical instrument can ablate renal nerves from outside of the renal artery safely and effectively and can overcome the depth-related limitations of the previous catheter-based system with less damage to the arterial walls. Method: We designed a looped bipolar electrosurgical instrument to be used with laparoscopy-based RDN system. The tip of instrument wraps around the renal artery and delivers the radio-frequency (RF) energy. We evaluated the thermal distribution via simulation study on a numerical model designed using histological data and validated the results by the in vitro study. Finally, to show the effectiveness of this system, we compared the performance of our system with that of catheter-based RDN system through simulations. Results: Simulation results were within the 95% confidence intervals of the in vitro experimental results. The validated results demonstrated that the proposed laparoscopy-based RDN system produces an effective thermal distribution for the removal of renal sympathetic nerves without damaging the arterial wall and addresses the depth limitation of catheter-based RDN system. Conclusions: We developed a novel laparoscope-based electrosurgical RDN method for hypertension treatment. The feasibility of our system was confirmed through a simulation study as well as in vitro experiments. Our proposed method could be an effective treatment for resistant hypertension as well as central nervous system diseases.